The effect of fiction on the well-being of older adults : a longitudinal RCT intervention study using audiobooks - Poerio, Giulia (Colegio Oficial de Psicólogos de Madrid, 2020)
Research has examined the psychological benefits of fiction, particularly for socio-cognitive and interpersonal processes, but has yet to examine whether it can have an impact on individuals personal well-being in a natural setting over time. A longitudinal randomized control trial (RCT) using audiobooks was conducted to compare the effects of fiction (novels, short stories) and non-fiction on the well-being (subjective, eudaimonic, social) of 94 older adults from diverse urban communities over a six-week period. Participants chose one of four books in the condition to which they were allocated. The participants in the fiction, compared to non-fiction, conditions did not show greater improvements in any aspect of well-being over the study period. However, regression analysis controlling for initial levels of well-being showed that individuals who reported greater absorption in, and appreciation of, their audiobook showed greater subsequent well- being, particularly meaning in life, that extended beyond book completion. The findings indicate that an audiobook can have a positive enduring impact on various aspects of older adults well-being, but it depends on them having a personal engagement with its content, and not on its designation as fiction or non-fiction.